2021
DOI: 10.1371/journal.pone.0250983
|View full text |Cite
|
Sign up to set email alerts
|

Maternal obesity and stillbirth at term; placental pathology—A case control study

Abstract: Objective The aim was to explore the potential role of the placenta for the risk of stillbirth at term in pregnancies of obese women. Methods This was a case-control study comparing placental findings from term stillbirths with placental findings from live born infants. Cases were singleton term stillbirths to normal weight or obese women, identified in the Stockholm stillbirth database, n = 264 and n = 87, respectively. Controls were term singletons born alive to normal weight or obese women, delivered betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…24 Corpulence increases the length of the umbilical cord accounting to hyper coiling, which increases the risk of cord entanglement, clogging of the umbilical cord, and umbilical knot around the foetus, reducing the blood flow and resulting in placental insufficiency, which causes foetal growth restriction and stillbirth. 25 Increased BMI may be a result of inheritance or a sedentary lifestyle. In order to minimize stillbirth, pregnant women should maintain a good height to body weight ratio.…”
Section: Obesitymentioning
confidence: 99%
“…24 Corpulence increases the length of the umbilical cord accounting to hyper coiling, which increases the risk of cord entanglement, clogging of the umbilical cord, and umbilical knot around the foetus, reducing the blood flow and resulting in placental insufficiency, which causes foetal growth restriction and stillbirth. 25 Increased BMI may be a result of inheritance or a sedentary lifestyle. In order to minimize stillbirth, pregnant women should maintain a good height to body weight ratio.…”
Section: Obesitymentioning
confidence: 99%
“…Population based studies showed the risk with increasing maternal body mass index (BMI) to be 2 to 14 times higher than in normal weight women, depending on the severity of obesity and the gestational age of pregnancy. Women with the aforementioned characteristics must be closely monitored [17][18][19] .…”
Section: Pathology Of Pregnancymentioning
confidence: 99%
“…It is one of the most important preventable causes of stillbirth [70]. A recent study suggests that umbilical cord abnormalities may account for approximately one-fourth of the effect of obesity on the risk of stillbirth at term [71]. Umbilical hyper coiling, velamentous and marginal cord insertion, thrombosis, and long cord have been described in obese women and all these complications are common causes of stillbirth [71].…”
Section: Umbilical Cord Alterations Related To Non-hypertensive Mater...mentioning
confidence: 99%
“…A recent study suggests that umbilical cord abnormalities may account for approximately one-fourth of the effect of obesity on the risk of stillbirth at term [71]. Umbilical hyper coiling, velamentous and marginal cord insertion, thrombosis, and long cord have been described in obese women and all these complications are common causes of stillbirth [71]. Moreover, low umbilical cord blood pH has been found in obese pregnant women, proving that obesity can be an independent risk factor for fetal acidosis at birth increasing newborn morbimortality [72].…”
Section: Umbilical Cord Alterations Related To Non-hypertensive Mater...mentioning
confidence: 99%